EFFECT OF SPIN COATING PROCESS MODIFICATIONS ON THE QUALITY AND PERFORMANCE OF CZTS THIN FILMS FOR PHOTOVOLTAIC APPLICATIONS - Mr.UmeshBhimaraoPagare,Prof.Dr. ChaudhariPavinRaghunath (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Copper Zinc Tin Sulfide (Cu₂ZnSnS₄ or CZTS) has emerged as a promising material for sustainable and cost-effective thin-film solar cells due to its ideal bandgap ( 1.5 eV), high absorption coefficient, and composition of earth-abundant, non-toxic elements. As a potential alternative to more expensive photovoltaic materials, CZTS offers significant advantages in terms of both environmental sustainability and scalability for large-scale production. This study aims to explore the influence of various modifications to the spin coating process on the morphological, structural, optical, and photovoltaic properties of CZTS thin films. Specifically, the investigation focuses on the effects of spin speed, spin duration, and post-deposition annealing conditions, which are key parameters that impact the final film quality and performance.To evaluate the films’ properties, a comprehensive set of characterizations was conducted, including X-ray diffraction (XRD) for phase analysis and crystallinity, scanning electron microscopy (SEM) for surface morphology and uniformity, atomic force microscopy (AFM) for surface roughness and texture analysis, UV-Vis spectroscopy for optical bandgap determination and light absorption characteristics, energy-dispersive X-ray spectroscopy (EDX) for elemental composition analysis, and current-voltage (I-V) measurements to assess photovoltaic performance.The results of this study demonstrate that specific spin coating parameters—such as spin speed, spin duration, and annealing temperature—have a profound influence on the crystallinity, surface uniformity, and optical properties of the CZTS films. For instance, optimal spin speeds led to improved film uniformity and crystallization, while longer spin durations facilitated better precursor spreading, ensuring consistent film thickness. Additionally, annealing conditions played a crucial role in enhancing the structural integrity and phase purity of the CZTS material. The films produced under optimized spin coating and annealing conditions exhibited improved optical bandgaps, better light absorption, and enhanced charge transport properties, leading to significantly higher photovoltaic efficiency.